2019
DOI: 10.1021/acs.jced.8b01203
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Isomerism on the Liquid–Liquid Phase Behavior of Mixtures of 1-Alkyl-3-methylimidazolium Bis((trifluoromethyl)sulfonyl)amide Ionic Liquids with Heptanol

Abstract: Systematic investigations on the liquid–liquid phase behavior of binary mixtures of ionic liquids (IL) of the type 1-alkyl-3-methylimidazolium bis­((trifluoromethyl)­sulfonyl)­amide (C x mimNTf2, x = 2, 4, 6, 8, and 10) with n-heptanol and its branched isomers 3-ethyl-3-pentanol and 2,4-dimethyl-3-pentanol have been performed. The phase diagrams were determined at atmospheric pressure in the temperature range (T) of 263–448 K by applying the cloud point method. The phase diagrams are analyzed in terms of well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 51 publications
1
26
2
Order By: Relevance
“…Chemical stability is sometimes a problem for measurements of phase diagrams as well. 51,57,60,61 In the present study, no signs of decomposition or chemical reaction were observed in any of the systems even at the highest temperatures considered.…”
Section: ■ Introductioncontrasting
confidence: 47%
See 4 more Smart Citations
“…Chemical stability is sometimes a problem for measurements of phase diagrams as well. 51,57,60,61 In the present study, no signs of decomposition or chemical reaction were observed in any of the systems even at the highest temperatures considered.…”
Section: ■ Introductioncontrasting
confidence: 47%
“…The phase diagrams are determined by combining the synthetic method with the cloud point method. While the procedure of sample preparation was improved during the past years, ,, the reader is referred to the most recent paper on this topic, which describes the actual state of the art in sample preparation for LLE mixtures. In brief, by using computer-assisted syringe pumps for sample sizes of 1–2 g, an overall uncertainty ( k = 2) in the mole fraction of U ( x IL ) = ± 10 –4 is achieved.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations